Metabolic networks of longevity - Houtkooper, Riekelt H. (2010)
Molecular and cellular networks implicated in aging depend on a multitude of proteins that collectively mount adaptive and contingent metabolic responses to environmental challenges. Here we discuss the intimate links between metabolic regulation and longevity, and outline novel approaches for analyzing and manipulating such links to promote human healthspan.